Microbial assisted phytodepuration for water reclamation: Environmental benefits and threats. (February 2020) - Riva, Valentina; Riva, Francesco; Vergani, Lorenzo; Crotti, Elena; Borin, Sara; Mapelli, Francesca
Abstract: Climate changes push for water reuse as a priority to counteract water scarcity and minimize water footprint especially in agriculture, one of the highest water consuming human activities. Phytodepuration is indicated as a promising technology for water reclamation, also in the light of its economic and ecological sustainability, and the use of specific bacterial inocula for microbial assisted phytodepuration has been proposed as a further advance for its implementation. Here we provided an overview on the selection and use of plant growth promoting bacteria in Constructed Wetland (CW) systems, showing their advantages in terms of plant growth support and pollutant degradation abilities. Moreover, CWs are also proposed for the removal of emerging organic pollutants like antibiotics from urban wastewaters. We focused on this issue, still debated in the literature, revealing the necessity to deepen the knowledge on the antibiotic resistance spread into the environment in relation to treated wastewater release and reuse. In addition, given the presence in the plant system of microhabitats (e.g. rhizosphere) that are hot spot for Horizontal Gene Transfer, we highlighted the importance of gene exchange to understand if these events can promote the diffusion of antibiotic resistance genes and antibiotic resistant bacteria, possibly entering in the food production chain when treated wastewater is used for irrigation. Ideally, this new knowledge will lead to improve the design of phytodepuration systems to maximize the quality and safety of the treated effluents in compliance with the 'One Health' concept. Highlights: Constructed wetlands can improve water reuse, especially in the least developed countries. Plant growth promoting bacteria can improve plant services and phytodepuration. Horizontal Gene Transfer is promoted in ecological niches pivotal for water cleanup. Antibiotic resistance diffusion is a challenging aspect of wastewater treatment.